TINJAUAN TERHADAP PELAKSANAAN PERJANJIAN KERJASAMA ANTARA PT. ANDIKA PERMATA SAWIT LESTARI (APSL) DENGAN KELOMPOK TANI NELAYAN ANDALAN (KTNA) DI DESA BONAI KECAMATAN BONAI DARUSSALAM (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Agreement law is part of the engagement law which is regulated in the third book of the Civil Code (KUHPer) entitled about engagement. One of the anatomy of agreement is Negotiation. Negotiation is a process to reach an agreement by giving consensus to one another (give and take). In a negotiation, what is being negotiated are the elements of the agreement and default (broken promise). One example of an agreement is that several small farmers form farmer groups, then collaborate and form a legal farmer group called the Andalan Fisherman Farmer Group (KTNA). Then the farmer group cooperates with PT. Andika Permata Sawit Lestari (APSL).This type of research is sociological legal research. Sociological legal research is research that is carried out directly in the location or in the field to obtain data in order to provide a complete and clear picture of the problem under study. This research is conducted at PT. Andika Permata Sawit Lestari (APSL) and Mainstay Farmers and Fishermen Group (KTNA) in Bonai Village, Bonai Darussalam District.The results of the research conducted by the author are legal measures by PT. Andika Permata Sawit Lestari (APSL) only compensates for the losses of the first party by fulfilling the first demands that do not or have not received the results. Therefore, negotiations between PT. Andika Permata Sawit Lestari (APSL) with the Mainstay Fisherman Farmers Group (KTNA) in Bonai Village, Bonai Darussalam District, which in connection with this is represented by the chairman of the Andalan Fisherman Farmers Group (KTNA), to clarify the contents of the cooperation agreement considering that every year there is a development of Family Cards ( KK) and so that the rights and obligations in the agreement can be carried out and fulfilled properly. And there should be clear legal remedies in overcoming problems in implementing the cooperation agreement between PT. Andika Permata Sawit Lestari (APSL) with the Mainstay Farmers and Fishermen Group (KTNA) in Bonai Village, Bonai Darussalam District.Keywords: Implementation, Cooperation Agreement.